Understanding social action, promoting human rights - Goodman, Ryan; Jinks, Derek; Woods, Andrew K. (Oxford University Press, 2013)
The editors bring together a stellar group of contributors from across the social sciences to apply a broad yet conceptually unified array of advanced social science research concepts to the study of human rights and human rights law.